Hubungan Pola Asuh Orang Tua dengan Tingkat Kecanduan Penggunaan Smartphone pada Anak Prasekolah di Sumedang - Aziziyah, Devi Nur; Rina, Nofha (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2025)
The use of smartphones today is not limited to adults and teenagers, but has been widely used by children, especially preschoolers. To monitor and prevent children from being addicted to smartphones, parenting is very important. The purpose of this study was to explain the relationship between parenting style and the level of addiction to smartphone use in preschool children at Kemala Bhayangkari 22 Kindergarten, Sumedang. The method used is descriptive quantitative method. The sample in this study was 92 parents of preschoolers at Kemala Bhayangkari 22 Kindergarten, Sumedang. Sampling uses a census sample that includes a population that is under 100 people. This study obtained the results of the T test that had been carried out, by obtaining a t count value of 39.129. This shows that H0 is rejected and H1 is accepted because t count t table (39.129 1.662). Based on the test results of the coefficient of determination of parenting style for preschool children at Kemala Bhayangkari 22 Kindergarten, Sumedang, there is a 94.4% relationship with the level of smartphone addiction. The rest is influenced by other factors such as self-control, sensation seeking, and self-esteem.